Study to assess the incidence and the level of knowledge about anemia among pregnant women - KRISHNAVENI K; MUHAMMED JASEEL K; SAMBATH KUMAR R (International Journal of Pharma and Bio Sciences, 2019)
Anemia can generally affect all but the worst affected are infants, school-age children, and women of reproductive age. This observational study was carried out in a tertiary teaching care hospital with antenatal care for a period of eight months from January to August 2018 among pregnant women to assess the knowledge, attitude and practice towards anemia by using suitable questionnaire. Out of 272 pregnant women, 95(34.9%) were in the age group of 21-25 years with maximum of secondary education 83(30.5%). About 198(72.8%) pregnant women had anemia and 158(58%) had previous history of anemia. About 81(42.2%) respondents were not taking iron supplementation during pregnancy and 68(35.4%) were not consuming iron rich diet. 129(47.4%) pregnant women had mild anemia, 47(17%) had moderate anemia and 22(8%) had severe anemia. A large number of pregnant women 238(87.5%) were aware about anemia, 213(78.3%) were not aware about hookworms infestation related with anemia. Knowledge towards signs, vulnerability, diet, antenatal visit towards anemia were good while knowledge towards causes, and perceived effects of anemia were poor. Attitude towards anemia is average and knowledge is good among the pregnant women. The study concluded that, most of the pregnant women were anemic, may be due to repeated pregnancy at short interval of less than 2 years, not properly adherent towards iron supplementation along with a lesser amount of practice and attitude.